2014
DOI: 10.1371/journal.pgen.1004269
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Power to Detect Genetic (Co)Variance of Complex Traits Using SNP Data in Unrelated Samples

Abstract: We have recently developed analysis methods (GREML) to estimate the genetic variance of a complex trait/disease and the genetic correlation between two complex traits/diseases using genome-wide single nucleotide polymorphism (SNP) data in unrelated individuals. Here we use analytical derivations and simulations to quantify the sampling variance of the estimate of the proportion of phenotypic variance captured by all SNPs for quantitative traits and case-control studies. We also derive the approximate sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
344
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(356 citation statements)
references
References 32 publications
12
344
0
Order By: Relevance
“…Even though precise h 2 SNP estimates could not be obtained, presumably because of the small sample size and the increased standard errors [Visscher PM et al, 2014], we found that a significant proportion of the phenotypic variance for both verbal and spatial WM accuracy (VNB, SNB) can be attributed to common genetic variation ( P  = 0.0003 and P  = 0.0004 respectively), with at least 38% of variance explained by all genotyped SNPs. Lower h 2 SNP was observed for sustained attention/vigilance ( P  = 0.03).…”
Section: Resultsmentioning
confidence: 54%
“…Even though precise h 2 SNP estimates could not be obtained, presumably because of the small sample size and the increased standard errors [Visscher PM et al, 2014], we found that a significant proportion of the phenotypic variance for both verbal and spatial WM accuracy (VNB, SNB) can be attributed to common genetic variation ( P  = 0.0003 and P  = 0.0004 respectively), with at least 38% of variance explained by all genotyped SNPs. Lower h 2 SNP was observed for sustained attention/vigilance ( P  = 0.03).…”
Section: Resultsmentioning
confidence: 54%
“…Although our study had low power to detect modest but possibly important correlations between specific pairs of cancers (28), the distribution of test statistics over all pairs of cancers deviated little from the null (Figure 1), suggesting that at most a small fraction have modest or high (eg, ρ > 0.3) correlations (Supplementary Tables 18-19, available online). Four pairs of sites that show notable correlation in our study are bladder and lung, testes and kidney, DLBCL and CLL, and DLBCL and osteosarcoma.…”
Section: Discussionmentioning
confidence: 79%
“…While genotype information is available for a subsample of the LifeLines study, the selection of data for the current study means that the sample available for genetic analyses is rather small (approx. 2000 per sex), and would be severely underpowered for any statistical approach using non-family members, particularly for the bivariate model [19].…”
Section: Methodsmentioning
confidence: 99%